Rumble of the coaster ghost - Cummings, Troy (New York, NY : Scholastic Inc., 2016)
Alexander's class is going on a field trip to an amusement park called Safety Land with really slow, boring rides-- but this is Stermont, and when a weird magician tells Alexander and his friends that the roller coaster is haunted things start to get a lot more interesting.
450
Keywords: Elementary schools -- Juvenile fiction; Friendship -- Juvenile fiction; Monsters -- Fiction; Roller coasters -- Fiction; Amusement parks -- Fiction; School field trips -- Fiction; Schools -- Fiction; Friendship -- Fiction